Effects of organic acids on adsorption characteristics of Cadmium on soil minerals - XIE Xiao-mei; WENG Di (浙江大学学报. 农业与生命科学版)
Effects of organic acids on adsorption characteristics of Cadmium on soil minerals were studied, the results showed: Effects of organic acids on the adsorption of cadmium on the minerals were almost similar, i. e. amount of adsorbed cadmium increased with increasing the concentration of low molecular weight organic acid in solution at lower concentration, and decreased at higher concentration. However, amount of adsorbed cadmium increased with increasing the concentration of humic acid in solution. Adsorbed percent of cadmium on the minerals increased remarkably with increasing pH of the solution existing humic acid, and higher than adsorbed percent under other conditions. Nearly 100% cadmium was adsorbed (pH>5.0), and there has larger difference in adsorbed amount of cadmium on minerals with low molecular weight organic acids ligand (pH<5.5), which was related to the types of organic acids and minerals. The adsorbed amount of cadmium on minerals increased with increasing pH of the solution (pH>5.5).